2012
DOI: 10.1002/jobm.201100653
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of a Bacillus thuringiensis strain S1/4 with large and efficient insecticidal activities

Abstract: The bacterium Bacillus thuringiensis was recognized for its entomopathogenic activities related to Cry and Cyt proteins forming the δ-endotoxins and some extracellular activities like the vegetative insecticidal proteins (VIP) and Cry1I. These activities may act specifically against diverse organisms and some of them typically characterize each strain. Here, we screened a set of 212 B. thuringiensis strains to search the higher insecticidal activities. These strains had bipyramidal and cubic crystal morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…2). Obtained results are in agreement with those of Huang et al (2005) and Sellami et al (2013) who revealed a significant loss of body weight in the third-instar larvae of Ostrinia nubilalis, Spodoptera littoralis, and Ephestia kuehniella after 3 to 4 days post exposure to Bt Cry1Ac andVip3 toxins.…”
Section: Toxicity Of Isolated Bt Strain To H Armigera Larvaesupporting
confidence: 80%
“…2). Obtained results are in agreement with those of Huang et al (2005) and Sellami et al (2013) who revealed a significant loss of body weight in the third-instar larvae of Ostrinia nubilalis, Spodoptera littoralis, and Ephestia kuehniella after 3 to 4 days post exposure to Bt Cry1Ac andVip3 toxins.…”
Section: Toxicity Of Isolated Bt Strain To H Armigera Larvaesupporting
confidence: 80%
“…Interestingly, the MEB4 strain was noted to induce the highest mortality rates against this lepidopteran larval insect, exhibiting an LC 50 value of 103,08 ± 36 µg g −1 , particularly when compared to the reference BNS3 strain (LC 50 of 120,432 ± 40,666 µg g −1 ). The detected insecticidal activity of the three strains (BLB140, BLB240 and MEB4) towards E. kuehniella could presumably be attributed to the mixture of Cry1 and Cry2 proteins as previously reported by Saadaoui et al and Sellami et al Furthermore, the differences observed in the insecticidal activities of the BLB140 and the MEB4 and BLB240 strains could be ascribed to the fact that Cry2 proteins were present only in the two latter strains, along with Cry1 toxins, and/or to a higher activity of their Cry1 proteins.…”
Section: Resultssupporting
confidence: 74%
“…It is considered as the most widely used microbial biopesticide (Sellami et al 2013) with insecticidal crystal proteins (ICPs), which are highly specific to target insect and innocuous to humans, plant and animals (Bravo et al 2007;Soberon et al 2009). Moreover, many Bt stains also have been reported to possess the potential of removal organic pollutants and heavy metal from water and soil environments (Brar et al 2009;Dave and Dave 2009;Kebria et al 2009;Muneer et al 2009;Zhuang et al 2011;Huang et al 2014).…”
Section: Introductionmentioning
confidence: 99%